1988
DOI: 10.1007/bf00332485
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and 7-ethoxyresorufin O-deethylase-inducing potency of coplanar polychlorinated biphenyls (PCBs) in chick embryos

Abstract: The toxicities of the coplanar polychlorinated biphenyls 3,3',4,4'-tetrachlorobiphenyl (TCB), 3,3',4,4',5-pentachlorobiphenyl (PeCB) and 3,3',4,4',5,5'-hexachlorobiphenyl (HCB) were compared in a 72-h study on chick embryos. The substances were injected into the air sacs of hens' eggs preincubated for 7 days. Mortality was measured 72 h later and corresponding LD50 values were calculated. The rank order of toxicity was PeCB greater than TCB greater than HCB. Using the same injection procedure, the potencies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
79
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 20 publications
17
79
1
Order By: Relevance
“…This order is similar to the typical Ah receptor-mediated response in the chicken embryo, i.e., cytochrome P4501A1 induction (Brunstrom and Andersson, 1988;Brunstrbm, 1988). The rank order for EROD induction by PCBs is 3, 3',4,4',5-pentaCB > 3,3',4,4'-tetraCB > 3,3',4,4',5,5'-hexaCB (Brunstrom and Andersson, 1988).…”
Section: Teq = 2 [Pcdd] X Tef + 2 [Pcdf] X Tefsupporting
confidence: 57%
See 2 more Smart Citations
“…This order is similar to the typical Ah receptor-mediated response in the chicken embryo, i.e., cytochrome P4501A1 induction (Brunstrom and Andersson, 1988;Brunstrbm, 1988). The rank order for EROD induction by PCBs is 3, 3',4,4',5-pentaCB > 3,3',4,4'-tetraCB > 3,3',4,4',5,5'-hexaCB (Brunstrom and Andersson, 1988).…”
Section: Teq = 2 [Pcdd] X Tef + 2 [Pcdf] X Tefsupporting
confidence: 57%
“…Several studies have reported that the chicken embryo is highly sensitive to the toxic effects of TCDD, coplanar PCB congeners, and related HAHs (Poland and Glover, 1977;Rifkind et al, 1984;Brunstrom and Andersson, 1988). The Ah receptor can be detected in 5-day-old embryos, and although receptor levels are variable in the embryo and neonate (Denison et al, 1986), induction of CYP1A1-dependent activity is observed throughout embryonic development and in the neonate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with chickens and wild avian species reported in vitro and in ovo effects, with REPs ranging from <0.0003 to 0.15 depending on the species (66,68,69,122,123). A value of 0.05 is recommended.…”
Section: Review Of Tefs Approach For Deriving Tefsmentioning
confidence: 99%
“…Schwartz et al (1993) reported 71 ng/g of PCB congener 126 in a bald eagle egg containing a deformed embryo. This concentration is over 10-fold higher than the LD50 in the chicken egg (Brunstrom and Andersson, 1988) and slightly higher than the LD50 in the American kestrel egg (Hoffman et al, 1995). Best et al (1994) and Bowerman et al (1994) have also related nest productivity to PCB concentrations in bald eagle eggs from the Great Lakes that failed to hatch.…”
mentioning
confidence: 95%